A conceptual framework to understand learning through formative assessments with student response systems: The role of prompts and diagnostic cues. Issue 1 (2022) - Molin, François; de Bruin, Anique; Haelermans, Carla
Abstract: The aim of this study is to develop a conceptual framework to identify relationships between factors that may be responsible for influencing metacognition when students are formatively assessed using educational technology such as student response systems. We describe and bridge the monitor and control model of Nelson and Narens (1990) and the cue utilization framework of Koriat (1997), which we complement with aspects from digital formative assessments. Based on this we develop a conceptual framework that may identify prompts and diagnostic cues of formative assessments using student response systems on metacognition. The framework provides insight into which prompts may influence the utilization of diagnostic cues and thereby learning. The developed framework suggests that more prompts lead to more diagnostic cues, which improve students' accuracy of monitoring judgments and enhanced metacognition. Highlights: What is already known about this topic: - Many teachers use polling systems in their formative assessments without realizing the extent to which this may affect student learning. - Metacognitive prompts are all helpful for students and teachers What this paper adds: - This study explains the mechanisms which might be responsible for influencing metacognition when students are formatively assessed using polling systems. - Formative assessments contain multiple metacognitive prompts. - Metacognitive prompts are helpful, as they identify one or more diagnostic cues that are predictive of subsequent learning. Implications for practice and/or policy: - The metacognitive framework makes explicit how students can accurately judge their learning when formative assessed by polling systems.